Thermodynamics of Dissociation and Micellization of Manganese Caprylate and Laurate in 70/30 (v/v) Benzene-Methanol Mixture - Upadhyaya, S.K.; S. Sharma, Prem (Asian Journal of Chemistry, 2012)
The conductivity results showed that manganese caprylate and laurate behave as weak electrolyte in dilute solutions and the micellization was found to be dominant over the dissociation process. The values of the critical micellar concentration of these soaps increase with an increase in temperature and the dissociation constant, degree of dissociation and limiting molar conductance were evaluated from conductivity measurements.